Editorial: Social, economic and political reality - El Director (2014)
This issue of the journal iecos includes research articles covering various dimensions of social, economic and political reality. In this way, the FIEECS Research Institute contributes to the national debate by presenting reflections based on evidence and with a diversity of approaches that is a constitutive part of the University's work.